Hepatocyte‐specific deletion of adipose triglyceride lipase (adipose triglyceride lipase/patatin‐like phospholipase domain containing 2) ameliorates dietary induced steatohepatitis in mice. Issue 1 (4th December 2021) - Fuchs, Claudia D.; Radun, Richard; Dixon, Emmanuel D.; Mlitz, Veronika; Timelthaler, Gerald; Halilbasic, Emina; Herac, Merima; Jonker, Johan W.; Ronda, Onne A. H. O.; Tardelli, Matteo; Haemmerle, Guenter; Zimmermann, Robert; et al.
Abstract: Background and Aims: Increased fatty acid (FA) flux from adipose tissue to the liver contributes to the development of NAFLD. Because free FAs are key lipotoxic triggers accelerating disease progression, inhibiting adipose triglyceride lipase (ATGL)/patatin‐like phospholipase domain containing 2 (PNPLA2), the main enzyme driving lipolysis, may attenuate steatohepatitis. Approach and Results: Hepatocyte‐specific ATGL knockout (ATGL LKO) mice were challenged with methionine‐choline–deficient (MCD) or high‐fat high‐carbohydrate (HFHC) diet. Serum biochemistry, hepatic lipid content and liver histology were assessed. Mechanistically, hepatic gene and protein expression of lipid metabolism, inflammation, fibrosis, apoptosis, and endoplasmic reticulum (ER) stress markers were investigated. DNA binding activity for peroxisome proliferator‐activated receptor (PPAR) α and PPARδ was measured. After short hairpin RNA–mediated ATGL knockdown, HepG2 cells were treated with lipopolysaccharide (LPS) or oleic acid:palmitic acid 2:1 (OP21) to explore the direct role of ATGL in inflammation in vitro. On MCD and HFHC challenge, ATGL LKO mice showed reduced PPARα and increased PPARδ DNA binding activity when compared with challenged wild‐type (WT) mice. Despite histologically and biochemically pronounced hepatic steatosis, dietary‐challenged ATGL LKO mice showed lower hepatic inflammation, reflected by the reduced number of Galectin3/MAC‐2 and myeloperoxidase‐positive cells and low mRNA expression levels of inflammatory markers (such as IL‐1β and F4/80) when compared with WT mice. In line with this, protein levels of the ER stress markers protein kinase R–like endoplasmic reticulum kinase and inositol‐requiring enzyme 1α were reduced in ATGL LKO mice fed with MCD diet. Accordingly, pretreatment of LPS‐treated HepG2 cells with the PPARδ agonist GW0742 suppressed mRNA expression of inflammatory markers. Additionally, ATGL knockdown in HepG2 cells attenuated LPS/OP21‐induced expression of proinflammatory cytokines and chemokines such as chemokine (C‐X‐C motif) ligand 5, chemokine (C‐C motif) ligand (Ccl) 2, and Ccl5. Conclusions: Low hepatic lipolysis and increased PPARδ activity in ATGL/PNPLA2 deficiency may counteract hepatic inflammation and ER stress despite increased steatosis. Therefore, lowering hepatocyte lipolysis through ATGL inhibition represents a promising therapeutic strategy for the treatment of steatohepatitis.